2012
DOI: 10.1042/cs20120042
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin and its receptors: pathophysiological implications

Abstract: Tissue angiotensin generation depends on the uptake of circulating (kidney-derived) renin and/or its precursor prorenin [together denoted as (pro)renin]. Since tissue renin levels are usually somewhat higher than expected based upon the amount of (renin-containing) blood in tissue, an active uptake mechanism has been proposed. Several candidates have been evaluated in the past three decades, including a renin-binding protein, the mannose 6-phosphate/insulin-like growth factor II receptor and the (pro)renin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 138 publications
0
41
0
Order By: Relevance
“…One such candidate, the so-called (pro)renin receptor ((P)RR), which binds both renin and prorenin, has received much attention during the last decade. 5 Unfortunately, the concentrations of renin/prorenin (together denoted here as (pro)renin) that are required to result in receptor binding are far above the normal (patho)physiological levels, and transgenic rodents overexpressing either the (P)RR or prorenin did not reveal any evidence for (pro)renin-(P)RR interaction in vivo, that is, their Ang II levels were unaltered. 6 Moreover, (P)RR knockout (KO), unlike renin KO, is lethal.…”
Section: What Is a Local Raas?mentioning
confidence: 99%
See 1 more Smart Citation
“…One such candidate, the so-called (pro)renin receptor ((P)RR), which binds both renin and prorenin, has received much attention during the last decade. 5 Unfortunately, the concentrations of renin/prorenin (together denoted here as (pro)renin) that are required to result in receptor binding are far above the normal (patho)physiological levels, and transgenic rodents overexpressing either the (P)RR or prorenin did not reveal any evidence for (pro)renin-(P)RR interaction in vivo, that is, their Ang II levels were unaltered. 6 Moreover, (P)RR knockout (KO), unlike renin KO, is lethal.…”
Section: What Is a Local Raas?mentioning
confidence: 99%
“…Classically, interference occurs at the level of renin, angiotensin-converting enzyme (ACE), the Ang II type 1 (AT 1 ) receptor (R), or the mineralocorticoid receptor (MR), with renin inhibitors, ACE inhibitors AT 1 receptor blockers (ARBs) or MR antagonists. Novel enzyme inhibitors now target aminopeptidase A (APA), which generates Ang III (=Ang- [2][3][4][5][6][7][8]) from Ang II (=Ang-1-8)), or aldosterone synthase (CYP11B2). Activators of ACE2 (XNT and diminazene), which generates Ang-(1-7) from Ang II, were recently found to act equally well in ACE2 knockout (KO) animals, thus questioning their mechanism of action.…”
Section: Local Effects Of Ang II In the Vessel Wallmentioning
confidence: 99%
“…[2][3][4][5][6] However, the physiological relevance of the (pro)renin-(P)RR interaction is questionable because the (pro)renin concentrations required are >1000× higher than observed under (patho) physiological conditions. 7,8 Recently, (pro)renin-independent functions for (P)RR have been reported, including a function as an accessory protein of the vacuolar H + -ATPase (V-ATPase). 9 V-ATPases are multisubunit complexes, and they are expressed virtually in all cells types.…”
mentioning
confidence: 99%
“…2 However, subsequent transgenic animal models failed to show a causal link between PRR and hypertension. [2][3][4][5] Instead, it has emerged that PRR is essential for cellular development and homeostasis. PRR is ubiquitously expressed, and total knockout in mice is embryonic lethal.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in many processes have been observed upon deletion of PRR. 5,12 These effects appear to be central to the molecular association of PRR with the vacuolar (V)-adenosine triphosphatase (ATPase), where it is proposed that PRR regulates V-ATPase activity. 13 Much insight into PRR function has come from developmental biology studies, which showed that the association of PRR with the V-ATPase is essential for canonical Wnt signaling, 13 an important developmental pathway.…”
Section: Introductionmentioning
confidence: 99%